Knowledge, attitudes and intentions of the Syrian pregnant women toward labour analgesia, and its associated factors: a cross sectional study in Syria (2022) - Haidara Bohsas; Hidar Alibrahim; Sarya Swed; Yasmeen Abouainain; Mohamad Nour Nasif; Nagham Jawish; Mohammad Bani Almarja; Sara Aldarwish; Carol Ghareeb; Bisher Sawaf; Wael Hafez (BMC, 2023)
Abstract Background During the reproductive period among pregnant women, the worst pain a woman can experience is labour pain. Untreated labour pain has many detrimental effects on the mother and the fetus. Then, the inadequate levels of awareness and attitudes toward labour analgesia among pregnant women are considered a serious concern that influences no-healthy results for both the mother and the baby. Therefore, this research aimed to define the degree of Awareness, Attitude, and intent to use labour analgesia among pregnant women in Syria. Methods We conducted a cross-sectional study from 7 September to 23 October 2022, in which we included Pregnant Syrian women aged 18 and above. The questionnaire was based on a prior study that included verified and validated scales, which consisted of 23 questions separated into four sections. The sample size was calculated using Fisher's formula; however, our study included 638 participants. The data was analyzed using IBM SPSS Version 28.0, using descriptive and binary logistic regression methods. Results Among those who had previous deliveries, 39.4% performed a caesarian delivery, and only 1.9% had a delivery at home. Nearly half of the study participants (50.4%) reported adequate knowledge about analgesia for obstetric pain. The inquired pregnant women who had children had more odds of knowledge than participants who had not. Respondents who were childbearing at the health center were more likely to have a good attitude (Adjusted Odds ratio = 4.728, P-value < 0.05, 95%CI: 1.035-21.589) than those who were childbearing at a national referral hospital. Also, the respondents above 31 years were less likely to desire labour analgesia than those aged 18-24. Conclusion Our results revealed that Syrian pregnant women have a moderated awareness, attitudes, and desire regarding labour analgesia, indicating a serious health problem among this population group. It is recommended that local and global health organizations address the current condition relevant to this issue by implementing healthy educational programmes for Syrian women through coordination with obstetric and gynaecological professionals.